Springtime Export of Arctic Sea Ice Influences Phytoplankton Production in the Greenland Sea. Issue 3 (14th March 2020) - Mayot, N.; Matrai, P. A.; Arjona, A.; Bélanger, S.; Marchese, C.; Jaegler, T.; Ardyna, M.; Steele, M.
Abstract: Climate model projections suggest a substantial decrease of sea ice export into the outflow areas of the Arctic Ocean over the 21st century. Fram Strait, located in the Greenland Sea sector, is the principal gateway for ice export from the Arctic Ocean. The consequences of lower sea ice flux through Fram Strait on ocean dynamics and primary production in the Greenland Sea remain unknown. By using the most recent 16 years (2003–2018) of satellite imagery available and hydrographic in situ observations, the role of exported Arctic sea ice on water column stratification and phytoplankton production in the Greenland Sea is evaluated. Years with high Arctic sea ice flux through Fram Strait resulted in high sea ice concentration in the Greenland Sea, stronger water column stratification, and an earlier spring phytoplankton bloom associated with high primary production levels. Similarly, years with low Fram Strait ice flux were associated with a weak water column stratification and a delayed phytoplankton spring bloom. This work emphasizes that sea ice and phytoplankton production in subarctic "outflow seas" can be strongly influenced by changes occurring in the Arctic Ocean. Plain Language Summary: As the Arctic atmosphere and ocean warm, Arctic sea ice continues to decline. The Greenland Sea (to the east of Greenland) is heavily influenced by sea ice leaving the Arctic Ocean. In this study, we address the impacts of sea ice exiting the Arctic on the development of free‐floating microscopic algae in the Greenland Sea. For this, we analyzed 16 years of data from satellite images and autonomous ocean robots. Our results reveal that changes in the quantity of sea ice leaving the Arctic Ocean in spring modify the environment and development of microscopic algae. These algae are important because they capture carbon dioxide and support ocean life; this paper can help to predict how they will respond to the ongoing environmental changes occurring in the Arctic. Key Points: A positive relationship exists between exported Arctic sea ice and the sea ice distribution in the Greenland Sea High (low) springtime export of Arctic sea ice may increase (reduce) the stratification of the Greenland Basin A strong (weak) salinity stratification of the Greenland Basin induces an early (late) phytoplankton spring bloom and primary production